SAFETY ISSUES AND RISKS IN THE SYSTEM "MAN - MACHINE - ENVIRONMENT" - and; and (Municipal economy of cities. Series: «Economy science», 2013)
The problems of security in the system "man - machine - environment" depending on the risk level of the production process.